2018
DOI: 10.1038/s41586-018-0075-5
|View full text |Cite
|
Sign up to set email alerts
|

De novo formation of the biliary system by TGFβ-mediated hepatocyte transdifferentiation

Abstract: Transdifferentiation is a complete and stable change in cell identity that serves as an alternative to stem-cell-mediated organ regeneration. In adult mammals, findings of transdifferentiation have been limited to the replenishment of cells lost from preexisting structures, in the presence of a fully developed scaffold and niche. Here we show that transdifferentiation of hepatocytes in the mouse liver can build a structure that failed to form in development-the biliary system in a mouse model that mimics the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
251
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(270 citation statements)
references
References 54 publications
17
251
2
Order By: Relevance
“…Previous studies have demonstrated that transdifferentiated cells, such as hepatocyte‐derived BECs, may revert back to their original cell type when liver injury has abated . Alternatively, it has been shown that with persistent need for transdifferentiated cells, such as in mice that lack the intrahepatic biliary system, hepatocyte‐to‐BEC conversion is permanent and stable for life . To determine if BEC‐derived hepatocytes would persist and further repopulate the liver, KO2 mice were allowed to recover on normal diet for either 3 or 6 months after CDE diet (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that transdifferentiated cells, such as hepatocyte‐derived BECs, may revert back to their original cell type when liver injury has abated . Alternatively, it has been shown that with persistent need for transdifferentiated cells, such as in mice that lack the intrahepatic biliary system, hepatocyte‐to‐BEC conversion is permanent and stable for life . To determine if BEC‐derived hepatocytes would persist and further repopulate the liver, KO2 mice were allowed to recover on normal diet for either 3 or 6 months after CDE diet (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Work in several mouse models has shown that the severe BD paucity resulting from impaired Notch signaling improves over time . Accordingly, we examined whether Jag1 +/− animals recover from biliary paucity with age.…”
Section: Resultsmentioning
confidence: 99%
“…Black waterproof ink (Higgins, Leeds, MA) was injected using a 3‐mL syringe attached to a 32‐gauge needle and the PE10 cannula. Liver was resected and dehydrated through a methanol series to benzyl alcohol benzyl benzoate 1:2 solution to clear liver for imaging . For details on rehydration and staining of the ink‐injected livers, see Supporting Materials.…”
Section: Methodsmentioning
confidence: 99%
“…Although many investigations have shown the potential for transdifferentiation through in vitro studies, few have demonstrated transdifferentiation in vivo , as shown by Schaub et al, with hepatocytes transdifferentiating into cholangiocytes . As background, in the setting of cholestatic liver injury, hepatocytes can undergo biliary differentiation to form reactive ductules.…”
mentioning
confidence: 99%